Does the extension of free time trigger spontaneous elaborative strategies in working memory? - Leproult, Inès; Lemaire, Benoît; Portrat, Sophie (Memory & Cognition, 2024)
Elaboration has emerged as a potential maintenance mechanism involved in the substantial contribution of long-term memory (LTM) to working memory (WM) performance. The objective of the current study was to determine whether elaborative strategies could be spontaneously implemented under favorable conditions. Across four experiments, the distribution of free-time periods was manipulated in a complex span task, while keeping the total amount of free time and cognitive load constant. As elaboration requires time to be set up, Experiment 1 elicited better WM performance in a condition with fewer long free-time periods compared to a condition with many short free-time periods. However, because this benefit did not persist during delayed recall, the following experiments aimed to further investigate this effect by manipulating factors supposed to modulate elaboration. In Experiment 2, half of the participants received no specific instructions regarding strategies whereas the other half were encouraged to use elaborative strategies. In Experiment 3, the to-be-maintained stimuli did or did not have LTM representations that are essential for elaboration (i.e., words or pseudowords). Finally, the last experiment used a self-strategy report to better understand the nature of the WM maintenance strategies spontaneously employed by participants. Despite a consistent effect of free time manipulation on WM recall, the explanatory assumption of elaboration was challenged by the unexpected lack of effect on LTM recall and on the type of strategy reported. Alternative explanations stemming from well-known factors influencing WM performance are discussed, and emphasis is placed on the potential contribution of direct semantic maintenance in WM.